Lyapunov Function and Exponential Trichotomy on Time Scales - Ji Zhang (Discrete Dynamics in Nature and Society)
We study the relation between Lyapunov function and exponential trichotomy for the linear equation 𝑥Δ=𝐴(𝑡)𝑥 on time scales. Furthermore, as an application of these results, we give the roughness of exponential trichotomy on time scales.